2010
DOI: 10.1111/j.1528-1167.2010.02578.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of 32 children with encephalopathy with status epilepticus during sleep, or ESES syndrome

Abstract: Summary Purpose:  To prospectively evaluate the efficacy of drug treatment and long‐term cognitive outcome in children with encephalopathy with status epilepticus during sleep (ESESS). Methods:  Thirty‐two children were diagnosed and prospectively followed up for at least 3 years at our unit between 1991 and 2007. Twenty‐seven children were included in the prospective treatment study with valproate (VPA) and 17 with VPA combined with ethosuximide (ESM). Treatment response of disappearance of electrical status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
100
1
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 33 publications
11
100
1
5
Order By: Relevance
“…This convention behind the seemingly almost identical acronyms is accepted practice by several authors (Sánchez Fernán-dez et al, 2012, Liukkonen et al, 2010. The same survey showed that appart from nomenclature, oppinions about the course, outcome and diagnostic criteria were also very heterogenous.…”
Section: Terminological and Conceptual Chaos Around Eses Cswsmentioning
confidence: 89%
See 2 more Smart Citations
“…This convention behind the seemingly almost identical acronyms is accepted practice by several authors (Sánchez Fernán-dez et al, 2012, Liukkonen et al, 2010. The same survey showed that appart from nomenclature, oppinions about the course, outcome and diagnostic criteria were also very heterogenous.…”
Section: Terminological and Conceptual Chaos Around Eses Cswsmentioning
confidence: 89%
“…Similarly, Tassinari et al (2012) relies on the secondary bilateral synchrony mechanism which was assumed to work classically (Tükel and Jasper, 1952) by involving secondarily thalamic and thalamo-cortical circuitry. However, asymmetric, unilateral, or more focal/regional discharges were frequently reported (Bureau, 1995;Saltik et al, 2005;Van Hirtum-Das et al, 2006;Kramer et al, 2009;Liukkonen et al, 2010;Sánches Fernández et al, 2012). The sleep discharges in LKS were also found almost always asymmetric, with a dominant hemispheric and regional distribution congruently to the language disturbances.…”
Section: Terminological and Conceptual Chaos Around Eses Cswsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these patients, 8 had surgery; five patients had callosotomy, one patient hemispherotomy, one parietooccipital resection, and one multiple subpial transection. The authors of this study suggested that surgical treatment options should be considered early in drug-resistant symptomatic ESES cases (58).…”
Section: Treatmentmentioning
confidence: 97%
“…Among the other conventional AEDs, the single or combined uses of valproic acid and ethosuximide have been reported to be beneficial in some studies. (33,58,59) However, some authors hold the view that the conventional AEDs play only a minimal role and the response of patients is incomplete and transitory (10,54). Response to treatment by short-term, high dose diazepam cycles was reported (32).…”
Section: Treatmentmentioning
confidence: 99%